2013
DOI: 10.1371/journal.pone.0059952
|View full text |Cite
|
Sign up to set email alerts
|

Differential Regulation of Matrix-Metalloproteinases and Their Tissue Inhibitors in Patients with Aneurysmal Subarachnoid Hemorrhage

Abstract: BackgroundMatrix metalloproteinases (MMPs) and their tissue inhibitors (TIMPs) are involved in vascular remodeling, (neuro)inflammation, blood-brain barrier breakdown and neuronal apoptosis. Proinflammatory mechanisms are suggested to play an important role during early brain injury and cerebral vasospasm after aneurysmal subarachnoid hemorrhage (SAH). This study aimed to analyze MMP-3, MMP-9, TIMP-1 and TIMP-3 in patients with SAH and their respective association with cerebral vasospasm (CVS).MethodsBlood sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 46 publications
1
17
0
Order By: Relevance
“…Four other studies examined the relationship between MMP‐9 levels and radiographic vasospasm in SAH patients. Of these, three reported an association between higher levels of blood MMP‐9 and cerebral vasospasm, while the other reported a nonsignificant trend toward higher CSF MMP‐9 levels and cerebral vasospasm. Taken together, these preclinical and clinical studies suggest, but do not definitively establish, a role for MMP‐9 in the pathophysiology of vasospasm and DCI after SAH.…”
Section: Discussionsupporting
confidence: 58%
“…Four other studies examined the relationship between MMP‐9 levels and radiographic vasospasm in SAH patients. Of these, three reported an association between higher levels of blood MMP‐9 and cerebral vasospasm, while the other reported a nonsignificant trend toward higher CSF MMP‐9 levels and cerebral vasospasm. Taken together, these preclinical and clinical studies suggest, but do not definitively establish, a role for MMP‐9 in the pathophysiology of vasospasm and DCI after SAH.…”
Section: Discussionsupporting
confidence: 58%
“…However, the increased secretion of both MMP-9 and its endogenous inhibitor TIMP-1 indicated that the hMDM secrete potentially deleterious and protective proteins at the same time in an effort to maintain tissue homeostasis. The balance between MMP-9 and TIMP-1 has been seen in other brain injury models including ALS (Louboutin et al 2011;Tsai et al 2011;Fischer et al 2013;Wu et al 2015) and may be a crucial factor in the regulation of tissue damage. Evidence for deleterious effects when the balance is changed was seen when proNGF was added to HIV.…”
mentioning
confidence: 92%
“…Fischer et al evaluated blood samples in 20 patients with aSAH and showed that MMP‐9 was higher in aSAH patients compared to healthy controls ( P < .001) and an increase in MMP correlated with occurrence of vasospasm ( P < .05).…”
Section: Resultsmentioning
confidence: 99%